2016
DOI: 10.1038/srep19938
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and proteomic analysis of shoot apical meristem transition from dormancy to activation in Cunninghamia lanceolata (Lamb.) Hook

Abstract: In contrast to annual plants, in perennial plants, the shoot apical meristem (SAM) can undergo seasonal transitions between dormancy and activity; understanding this transition is crucial for understanding growth in perennial plants. However, little is known about the molecular mechanisms of SAM development in trees. Here, light and transmission electron microscopy revealed that evident changes in starch granules, lipid bodies, and cell walls thickness of the SAM in C. lanceolata during the transition from dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…Moreover, the same gene was also highlighted as a candidate gene for proteomic analysis of shoot apical meristem transition from dormancy to activation in Cunninghamia lanceolata (Lamb.) Hook [42]. In that study, the comparison of the reactivating and active stages with the dormant stage of shoot apical meristem demonstrated that higher levels of proteins involved in translation were present, results that provide further support for the involvement of the translation elongation factor 1α gene in the processes associated with bud burst and sprouting.…”
Section: A High Input Of Energy Is Required During Bud Sprouting In Cmentioning
confidence: 61%
“…Moreover, the same gene was also highlighted as a candidate gene for proteomic analysis of shoot apical meristem transition from dormancy to activation in Cunninghamia lanceolata (Lamb.) Hook [42]. In that study, the comparison of the reactivating and active stages with the dormant stage of shoot apical meristem demonstrated that higher levels of proteins involved in translation were present, results that provide further support for the involvement of the translation elongation factor 1α gene in the processes associated with bud burst and sprouting.…”
Section: A High Input Of Energy Is Required During Bud Sprouting In Cmentioning
confidence: 61%
“… Tarancón et al (2017) proposed that growth cessation and bud dormancy are consequences of carbon supply starvation syndrome linked to the sugar deficit. Over dormancy progression, and in response to winter conditions, soluble compounds (sucrose, glucose) are synthesized from the reserves accumulated during the growing season, such as starch grains ( Felker et al, 1983 ; Guzicka, 2001 ; Xu et al, 2016 ; Guzicka et al, 2017 ). Interestingly, poplars overexpressing sucrose phosphate synthase – which accumulate more sucrose and starch than the wild-type poplars – are characterized by accelerated bud break, raising the possibility that enhanced sugar and/or starch reserves can promote accelerated dormancy breaking ( Park et al, 2009 ).…”
Section: Carbohydrates Metabolismmentioning
confidence: 99%
“…Later, between 1980 and 2000, physiological studies including metabolic analyses led to further description of the main pathways involved, more recently highlighted by genetic and genomic studies. Numerous studies, notably transcriptomic analyses, have led to the identification of common molecular pathways regulating bud dormancy in trees ( Rohde et al, 2007 ; Ruttink et al, 2007 ; Yamane et al, 2008 ; Jiménez et al, 2010 ; Leida et al, 2010 ; El Kayal et al, 2011 ; Liu et al, 2012 ; Bai et al, 2013 ; Zhong et al, 2013 ; Xu et al, 2016 ; Tarancón et al, 2017 ). Specific gene expression patterns over the course of dormancy featured hormone signaling, carbon metabolism, stress response and chromatin modification ( Regier et al, 2010 ; Rios et al, 2014 ; Saito et al, 2015 ; Wisniewski et al, 2015 ; Wen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Periodic acid Schiff staining revealed that active and dormant bud stages showed increased numbers of large starch granules while less of them was found in reactivating buds [64]. TEM observations revealed differential morphology of lipid bodies, cell wall and plasmodesmata.…”
Section: Tem Observations Explain Differential Abundance Of Metabolicmentioning
confidence: 98%
“…These cytological changes were reflected by proteome remodeling, particularly by overabundance of proteins involved in, cell proliferation and translation and lower abundance of cytoskeletal proteins. In addition, dormancy release was accompanied by changes in proteins involved in photosynthesis, redox regulation, energy production and conversion, stress response and cytoskeleton [64].…”
Section: Tem Observations Explain Differential Abundance Of Metabolicmentioning
confidence: 99%